Chemical and elementary characterization of Spongiophyton nanum: Understanding the phylogeny, paleoenvironment, and fossilization processes of an enigmatic flora - Gaia, Geovane; Ribeiro, Victor Rodrigues [UNESP]; Ghilardi, Renato Pirani [UNESP]; Sousa, Felipe Nascimento [UNESP]; Llopart, Marta Pereira [UNESP]; Ricardi-Branco, Fresia (Elsevier, 2023)
The record of thalloid macrofossils in the North-Northwest region of the Paraná Basin is less studied compared to that of invertebrate paleofauna in the same area. Consequently, the lack of important information regarding the niches occupied by thalloid embryophytes during early land colonization in this coastal paleoenvironment is evident. This study presents the first chemical and elemental data on Spongiophyton for this region of the basin, offering insights into its paleoenvironment and fossilization processes and providing considerations about the phylogeny of this enigmatic assemblage Spongiophyton nanum Kräusel emend. Chaloner et al. (1974) collected fragments from an outcropping rock in Jaciara, Mato Grosso, Brazil, and studied them using scanning electron microscope/energy X-ray dispersive spectrometer (EDS) and Fourier transform infrared (FTIR) spectroscopy techniques. The EDS analysis showed the highest elemental concentration of carbon, oxygen, and calcium as the main elements of the cuticle composition. Silicon and aluminum were better represented inside the pores than in other areas of the cuticle. The high carbon concentration in the cuticle suggested an anoxic condition prevalent during the deposition of the fine-grained sediments, which prevented its oxidation before and during diagenesis. The carbon present in the EDS spectra was restricted to the cuticle area, and the FTIR spectra indicated the presence of some functional groups, both related to the original organic matter, possibly cutin. Based on elemental characterization, the fossilization of S. nanum may involve more than one process, such as carbonification and mineralization, and S. nanum has more affinities with lichen groups.
Keywords: Early land plant; FTIR; Paleoenvironment; SEM/EDS; Taphonomy